Exuberant hypercementosis mimicking cementoblastoma - Paredes, Silvia Y.; Silveira, Heitor A. [UNESP]; Almeida, Luciana Y. [UNESP]; Silva, Evânio V. [UNESP]; Trivellato, Alexandre Elias; Sverzut, Cassio E.; León, Jorge E. (GN1 Sistemas e Publicacoes, 2021)
Hypercementosis is a non-neoplastic proliferation involving excessive cementum deposition along the normal root cementum. Here, we report an unusual case of exuberant hypercementosis associated with chronic suppurative inflammation. A 77-year-old man sought dental care presenting a gingival suppurative lesion with several months of evolution. The radiographic examination showed a large radiopaque area involving the root of the tooth #46 surrounded entirely by a radiolucent area, suggesting cementoblastoma associated with infectious process. The histopathological examination of the involved tooth revealed an extensive hypercementosis associated with chronic suppurative inflammation and localized chronic osteomyelitis. This is an unusual presentation and due to the clinicopathological findings, the term “chronic hypercementitis” is proposed. Dentists, especially oral pathologists and endodontists, should be aware of this unusual presentation in order to establishing the correct diagnosis.
Hipercementose exuberante simulando cementoblastoma
Keywords: Differential diagnosis; Hypercementosis; Mandible; Oral pathology; Osteomyelitis